Use of Coontail as a Natural Phytoremediation Feed Additive for Common Carp - Kiziloğlu Ümmühan; Yıldırım Önder; Çantaş İsmail Berat (Oceanological and Hydrobiological Studies)
Ceratophyllum demersum is a submerged, rootless, free-floating macrophyte and natural aquatic phytoremediation. C. demersum has high efficiency in absorbing large amounts of nitrogen and phosphorus in the aquatic environment. In this study, the effects of a natural phytoremediation Ceratophyllum demersum meal, as a dietary supplement, on growth performance, feed utilization, and body composition of common carp (Cyprinus carpio L., 1758) were investigated. This was the first attempt to use coontail as a feed additive for common carp. Four isonitrogenous (38% crude protein), isolipidic (8% crude lipid), and isoenergetic (18 kJ g−1) diets were formulated control group (0%), CM5 group (5%), CM10 group (10%) and CM15 group (15%) in feed. Each dietary treatment was administered to triplicate in groups of 15 fish (~19 g). Carp were hand-fed to apparent saturation three times a day (09.00; 12.00 and 17.00). There was no difference between the control diet and 5% CM in terms of growth (final weight, weight gain, specific growth rate) and feed utilization (feed conversion rate, feed intake, feed efficiency) (p < 0.05). Increasing algae levels in diets improved protein levels in body compositions while decreasing lipid. There was no sign of appeared fish health indicators (disease or deformity) in all diet groups. This study results showed that instead of soybean meal, 5.75% and 6.07% as natural phytoremediation, C. demersum optimized the best growth and feed utilization performance in carp diets.